Analysis of Competency Improvement Students of SMK Negeri 1 Surakarta through Tukuya.id Marketplace: A Case Study of B2B Model Implementation in Teaching Factory - Martama, Happy; Jatmika, Surya (Pedagogia : Jurnal Pendidikan, 2024)
Tukuya,id Marketplace is a teaching factory innovation, specifically a marketplace that implements a business-to-business (B2B) interaction model at SMK Negeri 1 Surakarta. This marketplace is a bridge between MSMEs, especially in the city of Surakarta. The conceptualization of Tukuya.id aimed to accommodate all the expertise programs in the school and foster collaboration among apprentice students from various expertise programs. This study aims to describe the tukuya.id marketplace as a means of increasing competence among students at SMK Negeri 1 Surakarta. This research uses case study research with a qualitative approach. The subjects of this research are educators who are pioneers and students who intern at Tukuya.id. The data was collected using semi-structured interviews. The validity of the data in this study is tested using the source triangulation method and the interactive model of Miles, Huberman, and Saldana is used for data analysis. The results of this study indicate an increase in vocational skills for students in various fields and cognitive improvements such as critical thinking and problem-solving skills.